2008
DOI: 10.1007/s10549-008-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms (SNPs) in TNF-LTA locus with breast cancer risk in Indian population

Abstract: TNF-LTA locus could serve as an important biomarker for breast cancer predisposition in Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 44 publications
3
47
4
Order By: Relevance
“…Two SNPs located at nucleotides À238 and À308 have been extensively researched on the susceptibility to a range of autoimmune disorders, including rheumatoid arthritis, 9 exfoliation glaucoma, 10 and many kinds of cancers. [11][12][13] The hypothesis that TNF-a-308 G4A may have important roles in the development of UC, CD, and CRC has been debated. The results of previous association studies were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Two SNPs located at nucleotides À238 and À308 have been extensively researched on the susceptibility to a range of autoimmune disorders, including rheumatoid arthritis, 9 exfoliation glaucoma, 10 and many kinds of cancers. [11][12][13] The hypothesis that TNF-a-308 G4A may have important roles in the development of UC, CD, and CRC has been debated. The results of previous association studies were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…LTA is a crucial proinflammatory cytokine, which has multiple functions in immune system as TNF-α. The LTA +252G allele has been reported to increased LTA production by phytohemagglutininactivated mononuclear cells in vitro and have higher secretary capacity and circulatory concentrations of TNF-α (Messer et al, 1991;Pociot et al, 1993;Kohaar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphotoxin-α (LTA, TNF-β) is a cytokine which has a close structural homology and about 30% amino acid sequence identity to TNF-α, which are both recognized by the same widely distributed cellular TNF receptors and have similar effects (Smith et al, 1994). It is produced by diverse kinds of cells including macrophages, NK cells, T and B cells, and tumor cells et al (Anderson et al, 2004) and postulated to play a role in pathogenesis of cancers (Kobayashi et al, 1997;Kohaar et al, 2009). TNF-α and LTA polymorphisms were reported to be associated with cancers (Pooja et al, 2010), which had draw many researchers' attentions to in the breast cancer study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated an association between the TNFB þ 252 G allele and a higher risk of breast cancer and sarcoidosis, demonstrating a pivotal role for TNF-b in host cellular immunity. [31][32][33] Moreover, both TNFA and TNFB gene polymorphisms have been shown to be associated with TNF-a generation potential. Thus, TNFA and TNFB gene polymorphisms may have functional significance in diseases whose pathogenetic mechanisms include TNF-a production.…”
Section: Discussionmentioning
confidence: 99%